2021
DOI: 10.1002/ajh.26171
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic expression of a chimeric murine‐human CALR oncoprotein allows the assessment of anti‐CALR antibody immunotherapies in vivo

Abstract: Myeloproliferative neoplasms (MPNs) are characterized by a pathologic expansion of myeloid lineages. Mutations in JAK2, CALR and MPL genes are known to be three prominent MPN disease drivers. Mutant CALR (mutCALR) is an oncoprotein that interacts with and activates the thrombopoietin receptor (MPL) and represents an attractive target for targeted therapy of CALR mutated MPN. We generated a transgenic murine model with conditional expression of the human mutant exon 9 (del52) from the murine endogenous Calr loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…While Jak2 mutant cells were reported to outgrow wt competitors, heterozygous Calr mutated HSCs did not show a significant proliferative advantage compared to wt cells. [6][7][8] In this study we observed a steady increase in myeloid peripheral blood chimerism in all groups with little expansion in the Calr group and strongest expansion in mice that received double mutant bone marrow. The results were similar on the HSC level.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…While Jak2 mutant cells were reported to outgrow wt competitors, heterozygous Calr mutated HSCs did not show a significant proliferative advantage compared to wt cells. [6][7][8] In this study we observed a steady increase in myeloid peripheral blood chimerism in all groups with little expansion in the Calr group and strongest expansion in mice that received double mutant bone marrow. The results were similar on the HSC level.…”
supporting
confidence: 54%
“…5 and the Calr-del52 transgenic mice were generated in our laboratory. 6 The Calr-del52 vav-iCre mice were further bred with Jak2-V617F mutant mice to generate mice expressing both mutations in the hematopoietic compartment. Blood parameters were measured on hematology analyzer scil Vet abc™ (Horiba ABX, Montpellier, France).…”
mentioning
confidence: 99%
“…Because the mutant CALR-MPL complex traffics to the cell surface, interest in therapeutically targeting mutant CALR using a mutant CALR blocking antibody ( Figure 1 C) has grown. Three recent studies reported the development and testing of therapeutic monoclonal antibodies targeting the C-terminal mutant CALR sequence in preclinical models, 136 , 137 , 138 with 1 of the studies also testing the antibody (4D7) against primary MPN cells in vitro and demonstrating reduced megakaryocyte proliferation, specifically in CALR -mutant (but not JAK2- mutant) cells. 136 Similar findings in primary MPN cells were recently reported for a fully human immunoglobulin G1–mutant CALR antibody (INCA033989) as a plenary abstract at the 2022 American Society of Hematology meeting.…”
Section: Calr-mutated Mpns Provide Novel Therapeutic Targetsmentioning
confidence: 99%
“…The mouse model utilized within this study shows safety and efficacy for a rapidly proliferating tumour that is mutant CALR dependent, however, is not a relevant disease model for MPN. Future studies should investigate efficacy in relevant heterozygous mouse models (Li et al , 2018; Balligand et al , 2020; Achyutuni et al , 2021), including evidence for fibrosis reversal. Additionally, the antibody that we have developed against the common neoepitope C‐terminus of CALR can be used in both insertion and deletion CALR mutation‐positive patients and appears to have minimal or no effects on normal cells ex vivo .…”
Section: Resultsmentioning
confidence: 99%